Moho and uppermost mantle structure in the Alpine area from S-to-P converted waves - R. Kind (Copernicus Publications, 2021)
In the frame of the AlpArray project we analyse teleseismic data from permanent and temporary stations of the Alpine region to study seismic discontinuities down to about 140 km depth. We average broadband teleseismic S-waveform data to retrieve S-to-P converted signals from below the seismic stations. In order to avoid processing artefacts, no deconvolution or filtering is applied, and S arrival times are used as reference for stacking. We show a number of north–south and east-west profiles through the Alpine area. The Moho signals are always seen very clearly, and negative velocity gradients below the Moho depth are also visible in a number of profiles. A Moho depression is visible along larger parts of the Alpine chain. It reaches its largest depth of 60 km beneath the Tauern Window. However, the Moho depression ends abruptly near about 13∘ E below the eastern Tauern Window. This Moho depression may represent the crustal trench, where the Eurasian lithosphere is subducted below the Adriatic lithosphere. East of 13∘ E an important along-strike change occurs; the image of the Moho changes completely. No Moho deepening is found in this easterly region; instead the Moho bends up along the contact between the European and the Adriatic lithosphere all the way to the Pannonian Basin. An important along-strike change was also detected in the upper mantle structure at about 14∘ E. There, the lateral disappearance of a zone of negative velocity gradient in the uppermost mantle indicates that the S-dipping European slab laterally terminates east of the Tauern Window in the axial zone of the Alps. The area east of about 13∘ E is known to have been affected by severe late-stage modifications of the structure of crust and uppermost mantle during the Miocene when the ALCAPA (Alpine, Carpathian, Pannonian) block was subject to E-directed lateral extrusion.